Roller-skating into the big city: A case study of migrant workers' informal leisure activity in Guangzhou, China. (27th May 2019) - Lin, Minhui; Graefe, Alan R.
Abstract: The focus of this study was roller-skating on the streets of Guangzhou, China. It examined the relationship between informal leisure activities among young migrant workers and public spaces. Using basic data collected from nonparticipatory observations, in-depth interviews, and questionnaire responses, this study investigated how young migrant workers came to understand Guangzhou through roller-skating in public spaces and how roller-skating aided their integration into the city. The study found that when faced with marginalization as roller skaters, the participants adopted a moderate bodily strategy: they constructed their own informal leisure spaces and endowed public spaces with new meanings through embodied practice. As a kind of informal leisure activity, roller-skating came to transform urban streets into meaningful places for young migrant workers to pursue group belongingness; in that way, they established their own identities and constructed a place identity with Guangzhou.